Implementasi Merdeka Belajar Dalam Meningkatkan Mutu Pembelajaran Matematika - agustin, intan silvia (Attadib: Journal of Elementary Education, 2023)
Merdeka Belajar is a new policy issued by the Ministry of Education and Culture of the Republic of Indonesia. The implementation of independent learning in the form of efforts given to each free education unit can innovate which is also of course adapted to the region of each education unit as an openness to the learning process from home which can later provide a learning experience without having to be required by completion standards and graduation standards. The purpose of this study is to determine the implementation of independent learning in improving the quality of mathematics learning.  This research is a literature study research with a qualitative approach that will be described descriptively. The data used are studies from scientific articles, papers, proceedings, and books that are in accordance with the research focus. The results and discussions obtained are that freedom of learning can: (1) make students and teachers more creative, innovative, and of course more advanced in the use of technology; (2) the freedom of students in obtaining information in learning so as to improve literacy, numeracy and logical thinking skills and improve student cognitive. As a result, mathematics learning becomes more advanced due to the implementation of independent learning.